Optical microphone based on Mach Zehnder interferometer - Ng, Qin Yi. (2010)
Optical microphone was proposed and characterization of optical microphone had been done. An optical fiber microphone based on Mach Zehnder Interferometer had fabricated to detect acoustic wave and pick-up sound from surrounding. Optical fiber microphone is immune to electromagnetic interference and capable to perform under harsh environment. These features enable optical fiber microphone to be used in Magnetic Resonance Imaging (MRI) room or industry surrounded by high electromagnetic field. Characterization of sensor are frequency response, sensitivity, self-noise and signal to noise ratio of optical fiber microphone based on Mach Zehnder Interferometer was presented. Overall, the optical fiber microphone can detect frequency range from 10Hz to 30MHz. The optical fiber microphone exhibits sensitivity of 93.4mV/Pa, a linear response up to 0.15Pa and signal to noise ratio of 21dB measured at 1 kHz. These parameters were taken using the experiment setup with speaker as acoustic source. Another setup was done using piezoelectric transducer as acoustic source where the optical fiber microphone indicates sensitivity of 30.129V/Pa and able to widen the frequency ranges for detection. Sound recording was done by using Mach Zehnder interferometer as microphone and save as sound file. Optical fiber microphone also has its applications in industry and medical applications.